Coiling free electron matter waves. (15th April 2019) - Pierce, J; Webster, J; Larocque, H; Karimi, E; McMorran, B; Forbes, A
Abstract: Here we demonstrate particle beams that spiral in free space devoid of external fields. The beams consist of electrons in two lobes that twist around each other along the optical axis, such that each electron can be described by a two-lobed probability distribution that rotates as it propagates. Furthermore, we demonstrate that this twisting distribution can undergo programmed periods of angular acceleration. These unusual states are produced by preparing each free electron wavefunction in a superposition of non-diffracting Bessel modes that carry orbital angular momentum using nanofabricated diffraction holograms. The holograms can encode nonlinear azimuthal phase so that the resulting electron probability distribution twists in space in a controllable manner, accelerating and decelerating during propagation, without any radiation. This work provides a new platform to explore the dynamics of electrons in magnetic fields, and opens the possibility of producing other types of particle beams with coiling geometries.